Analysis of Volatile Compounds in Coffee Prepared by Various Brewing and Roasting Methods - Ja-Myung Yu; Mingi Chu; Hyunbeen Park; Jooyeon Park; Kwang-Geun Lee (Foods, 2021)
Volatile compounds of coffee brewed under various roasting conditions and by different brewing methods were analyzed. Green coffee beans (Coffea arabica) were roasted at 235 °C for 13 min, 240 °C for 15 min, and 245 °C for 17 min. Roasted coffee beans were ground into particles of three different sizes (710, 500, and 355 μm) and brewed by an espresso coffee machine and the cold brew method. Three types of water (filtered, tap, and bottled) were used for coffee extraction. SPME-GC-MS results indicated that increasing the roasting temperature and time increased the levels of 2,2′-methylene-bis-furan, guaiacol, and 4-ethylguaiacol (p < 0.05) and decreased the levels of furfural (p < 0.05). Grind size was inversely proportional to the measured signal of volatiles by GC-MS (p < 0.05). The measured GC/MS intensities of 2-methylpyrazine, 2,5-dimethylpyrazine, and 2-methoxy-4-vinylphenol were significantly higher in coffee brewed with filtered water (p < 0.05) than tap and bottled water. 2-Methylpyrazine, 1-methylpyrrole, and 2-acetylfuran were the most abundant components in the cold brew. Overall, roasting conditions and extraction methods were determined to be significant factors for volatile compounds in coffee. This is the first study showing the analysis of volatile compounds in coffee according to various types of water and extraction methods, such as espresso and cold brew coffee.